Investigating the Correlation Between Iraqi EFL Secondary School Students’ Willingness to Communicate and Their Writing Performance" - Dr. Balqees Hameedi Kadhim (Journal of College of Education, 2025)
Due to the significance of foreign language learning and its crucial role in fostering meaningful and effective communication, contemporary language learning pedagogy places considerable emphasis on learners’ willingness to communicate within foreign language classes, viewing it as a key indicator of their engagement and language acquisition. Therefore, this research aims to explore the correlation between the Iraqi EFL secondary school students’ willingness to communicate and their writing performance. To fulfil the objectives of the study, a sample of (100) female fourth-grade students were chosen randomly from three public secondary school, during the academic year 2024/2025. To collect and analyze data, two instruments were employed: a questionnaire adopted from Weaver (2005) and writing performance test. The results achieved indicate that Iraqi EFL secondary students show a greater willingness to communicate when working on writing tasks.
Keywords: SL/FL secondary students, Willingness to communicate (WTC), Self- Perceived Communication Competence (STCC)